The New Testament and criticism - Ladd, George Eldon, 1911-1982 (Grand Rapids, MI Eerdmans, 1967)
Contents: How is the Bible the word of God? -- What is criticism? -- Textual criticism -- Linguistic criticism -- Literary criticism -- Form criticism -- Historical criticism -- Comparative religions criticism. Includes bibliographical references and indexes.
Keywords: Bible. N.T. -- Criticism, interpretation, etc